2020
DOI: 10.1177/0003319720918509
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Stiffening Is an Extraintestinal Manifestation of Inflammatory Bowel Disease: Review of the Literature and Expert Panel Statement

Abstract: Current guidelines state that systemic inflammation, together with endothelial dysfunction, calcification, and hypercoagulability, predispose to premature atherosclerosis in patients with inflammatory bowel disease (IBD). We assessed whether IBD can affect aortic stiffness, a well-recognized vascular biomarker and an independent risk factor for cardiovascular (CV) disease (CVD) in several populations. Recent studies reported that aortic stiffness is increased in adults with IBD compared with matched controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 83 publications
1
22
0
3
Order By: Relevance
“…46 Studies reviewed in this article show that these pathologic events happen in a wide variety of CV and non-CV diseases through different mechanisms. 47…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Studies reviewed in this article show that these pathologic events happen in a wide variety of CV and non-CV diseases through different mechanisms. 47…”
Section: Discussionmentioning
confidence: 99%
“…46 Studies reviewed in this article show that these pathologic events happen in a wide variety of CV and non-CV diseases through different mechanisms. 47 In patients with diabetes mellitus, it is suggested that the accumulation of advanced glycation end products in the aortic wall is responsible for the changes in compliance. 48 The products of nonenzymatic glycation of proteins and lipids were increased in patients with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in IBD patients, increased aortic stiffness may mediate the CV manifestations of blood pressure, IHD, and cerebrovascular events. 95…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Their use in CID has been associated with improved bone mineral density and cardiovascular outcomes. (32)(33)(34)(35) Bone loss in CID is driven by both suppressed bone formation and enhanced bone resorption, and TNF-alpha inhibitor therapy has been shown to normalise markers of bone turnover. (36,37) Given the hypothetical links between CPP and bone turnover, we hypothesised that treatment of active CID with infliximab would lower circulating CPP levels and be temporally related to changes in markers of bone turnover.…”
Section: Introductionmentioning
confidence: 99%